The longitudinal impact of patient navigation on equity in colorectal cancer screening in a large primary care network. Issue 13 (1st April 2014) - Percac‐Lima, Sanja; López, Lenny; Ashburner, Jeffrey M.; Green, Alexander R.; Atlas, Steven J.
Abstract : BACKGROUND: The long‐term effects of interventions to improve colorectal (CRC) screening in vulnerable populations are uncertain. The authors evaluated the impact of patient navigation (PN) on the equity of CRC prevention over a 5‐year period. METHODS: A culturally tailored CRC screening PN program was implemented in 1 community health center (CHC) in 2007. In a primary care network, CRC screening rates from 2006 to 2010 among eligible patients from the CHC with PN were compared with the rates from other practices without PN. Multivariable logistic regression models for repeated measures were used to assess differences over time. RESULTS: Differences in CRC screening rates diminished among patients at the CHC with PN and at other practices between 2006 (49.2% vs 62.5%, respectively; P  < .001) and 2010 (69.2% vs 73.6%, respectively; P  < .001). The adjusted rate of increase over time was higher at the CHC versus other practices (5% vs 3.4% per year; P  < .001). Among Latino patients at the CHC compared with other practices, lower CRC screening rates in 2006 (47.5% vs 52.1%, respectively; P  = .02) were higher by 2010 (73.5% vs 67.3%, respectively; P  < .001). Similar CRC screening rates among non‐English speakers at the CHC and at other practices in 2006 (44.3% vs 44.7%, respectively; P  = .79) were higher at the CHC by 2010 (70.6% vs 58.6%, respectively; P  < .001). Adjusted screening rates increased more over time for Latino and non‐English speakers at the CHC compared with other practices (both P  < .001). CONCLUSIONS: A PN program increased CRC screening rates in a CHC and improved equity in vulnerable patients. Long‐term funding of PN programs has the potential to reduce cancer screening disparities. Cancer 2014;120:2025–2031 . © 2014 American Cancer Society . Abstract : A patient navigation program for colorectal cancer screening improves equity in cancer care for vulnerable patients over a 5‐year period. Colorectal cancer screening rates among Latino and non‐English–speaking patients at a practice with patient navigation increase over time and become significantly higher than in practices without patient navigation.